2017
DOI: 10.1097/prs.0000000000003244
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of the Superior and Inferior Labial Arteries: Impact for Safe Upper and Lower Lip Augmentation Procedures

Abstract: Based on the results of this investigation, a safer location for the application of volumizing material is the subcutaneous plane in the paramedian location of both the upper lip and the lower lip. Care has to be taken when aiming to inject in the midline, as the artery can be identified more frequently in superficial positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 20 publications
(22 reference statements)
0
27
0
Order By: Relevance
“…The vascular patterns in the skin of the upper lip (intermediate skin zone between the nose and the upper vermilion border) and lower lip (skin zone just beneath the lower vermilion border) have been studied ultrasonographically [5]. In addition, macroscopic observations of the locations of the arteries throughout the entire lip have also been reported, but those studies focused only on the larger arteries situated deeper in the tissue, not on the superficial blood vessels in the vermilion [6]. Neither of those studies examined the blood vessels in the lip vermilion or the effect of aging on those vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular patterns in the skin of the upper lip (intermediate skin zone between the nose and the upper vermilion border) and lower lip (skin zone just beneath the lower vermilion border) have been studied ultrasonographically [5]. In addition, macroscopic observations of the locations of the arteries throughout the entire lip have also been reported, but those studies focused only on the larger arteries situated deeper in the tissue, not on the superficial blood vessels in the vermilion [6]. Neither of those studies examined the blood vessels in the lip vermilion or the effect of aging on those vessels.…”
Section: Introductionmentioning
confidence: 99%
“…A specific body of evidence for aesthetic medicine practitioners is gradually being accumulated that can help inform them and avoid vascular complications. For example, Cotofana et al [31] performed a comprehensive cadaveric study of the superficial vasculature of the lip that was designed to provide clinicians with a framework for avoiding vascular occlusion. Additionally, a practitioner's years of experience appear to correlate with the lifetime risk of performing an inadvertent intravascular injection [32].…”
Section: Discussionmentioning
confidence: 99%
“…32 The vasculature of the lips is also highly variable, and the course of the superior and inferior labial arteries within the upper and lower lips is not always submucosal (between the oral mucosa and the orbicularis oris muscle). 36 A study of 193 cadavers reported labial artery position as submucosal in 78.1% of cases, intramuscular in 17.5% of cases, and subcutaneous in 2.1% of cases. The course of the arteries also switched between planes at least once in around a third of the cadavers, with the greatest variability observed in the midline location.…”
Section: Anatomical Considerationsmentioning
confidence: 99%